Shared-control for the kinematic model of a rear-wheel drive car - Jiang,J; Astolfi,A (IEEE, 2015)
This paper presents a shared-control algorithm for the kinematic model of a rear-wheel drive car, for which the set of feasible Cartesian positions is defined by a group of linear inequalities. The shared-control scheme is based on a hysteresis switch and its properties are established by a Lyapunov-like analysis. Simple numerical examples demonstrate the effectiveness of the shared-control law.